Pengembangan Kepribadian Guru - Nursyamsi, Nursyamsi (AT-TA'LIM, 2014)
The close relationship between students and a teacher is psychologically important in the school teaching and learning process. The teacher’s personality and character serves as model and becomes the source of inspiration for the students.  The quality of psychological relationship between students and teacher can only be realized if it is supported by teacher’s good personality. It is the quality of teacher’s total attitude and behaviour, and therefore, constitutes the main requirement for optimum teaching and learning process. The original meaning of the term ‘personality’ as quoted from the experts suggests that it is a dynamic organization of psychopysic that determines one’s behaviour, thoughts, and character.  Such character and personality can be identified as an individual quality which is manifested through consistence behavioural patterns in respond to the environment.  In Islamic point of view, one’s personal behaviour and attitude is determined by his or her obedience to the God alone. A teacher’s honor is part of his or her most important personality in realizing his/her professional tasks.  Therefore, he or she must be able to recognize and develop this personal pride as well as possible.Copyright © 2014 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v21i1.70